Exotic leather from broiler chicken leg skin: Processing and characterization - Fatama, Kanish; Alam, Md Nur E; Akter, Nasifa; Tamanna, Al; Hossain, Md Khabir; Chowdhury, Fariha; Azad, Md Abul Kashem; Saha, Madhu Sudan; Chakma, Shimul (Bangladesh Journal of Scientific and Industrial Research, 2025)
Broiler chicken leg skin (Cobb-500) is investigated in this study as an unconventional raw material for exotic leather production in Bangladesh. The raw skin contains 65.5% moisture, 28.4% protein, 6.2% fat, and 9.9% ash. Three tanning systems—chrome, semi-chrome, and vegetable—were applied to produce finished leathers, and their physicochemical and structural properties were evaluated. Thermogravimetric analysis revealed that chrome-tanned leather exhibited the highest thermal stability, with collagen degradation onset at ~350°C and ~20% residual chromium oxides, while vegetable-tanned samples degraded earlier with <5% residue. Mechanical testing showed chrome tanning achieved superior performance, with tensile strength (105 kg/cm²), tear strength (19.9 kg/cm²), elongation (19.3%), and shrinkage temperature (101°C). SEM micrographs confirmed compact, well-organized fiber bundles in chrome-tanned leather, contrasting with denser, less flexible structures in vegetable-tanned samples. Chicken leg skin shows strong potential as a renewable, durable leather source, promoting waste utilization and sustainable materials. Bangladesh J. Sci. Ind. Res. 60(4), 287-296, 2025